Tumor properties mediate the relationship between peripheral blood monocytes and tumor-associated macrophages in breast cancer - Stakheyeva, Marina N.; Patysheva, Marina R.; Kaigorodova, Evgeniya V.; Zavyalova, Marina V.; Tarabanovskaya, Natalia A.; Choynzonov, Evgeny L. 1952-; Cherdyntseva, Nadezhda V. (Cancer investigation)
In cancer patients, circulating monocytes show functional alterations. Since monocytes are precursors of tumor-associated macrophages (TAMs), TAMs ensuring tumor viability are potentially replenished through the recruitment of monocytes with specific properties. We demonstrated that locoregional metastasis and circulating factors, such as CD45-EpCAM + CD44 + CD24-/low circulating tumor cells, and serum MCP-1 and HMGB1 were statistically associated with modulation of the monocyte features in breast cancer patients. The count of circulating CD45-EpCAM + cells correlated with CD68+, CD163 + monocyte in blood, and with density of CD68 + TAM in breast cancer tumors. Overall, the relationship between monocytes and TAMs is mediated by the tumor in breast cancer patients.